(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article covers concepts of form-making in architecture, art and design in the late 19th and the early 20th centuries. The focus lies on study of interconnection between internal structure and exterior form in organic and inorganic objects, which seems more relevant than simple reproduction and replication of natural forms. Study of such changes provided the basis for a trend of metabolism dating back to the middle 20th century in architecture and urban planning in Japan, biomorphism in design and morphogenesis in America. Those theoretical and methodological concepts of form-making greatly affected designing efforts of architects and designers throughout the world. Regrettably, that did not have a considerable effect on understanding general laws of form-making and composition in the Soviet and post-Soviet periods of architectural and artistic training. A large number of publications dedicated to study of general laws, principles or categories of composition does not view them as interconnected with objective laws of form-making. Such approach distorts development of an integral system of knowledge of artistic and visual formmaking in architects- and designers-to-be Purpose of Research is to clarify the notions of “composition”, “laws of composition”, “general laws of composition”, their number and connection with form-making laws (morphogenesis). The following objectives have been set to achieve the purpose: - to study some concepts providing an insight into form-making (morphogenesis) in architecture and design; - to identify interconnection between laws of form-making and general laws of composition. Key notion in one or another theoretical and methodological concept of application of innovative processes in designing efforts of architects and designers is the notion of morphogenesis. In architecture and design morphogenesis may serve as a synonym of formmaking, envisaging the process of occurrence and transformation of an optimum form of an object on the whole. The notions “form-making” and “composition” have a similar understanding of the process of creating a new form, a new reality, a new product in architecture, design and art. Interconnection of general laws of composition and general laws of nature was pointed out by many scholars and artists. Relying on general laws of nature, we define five laws of formmaking. From this perspective it is fair to say that the essence and number of general laws of composition as a key component of art, architecture and design are determined by laws of formmaking.